Antinutritional Evaluation and In vitro Protein Digestibility of Some Nigerian Cucurbits - Franca, Okoye Ngozi (Pakistan Journal of Nutrition, 2012)
The antinutritional factors of three Nigerian cucurbits namely, ‘snake tomato’ Trichosanthes cucumerina, ‘pumpkins’ Cucurbita pepo and Cucurbita moschata were analyzed. The antinutritional factors evaluated were tannin ranging from 0.23 to 0.49%; oxalate, 0.01 to 0.23%; cyanogenic glycosides, 0.43 to 0.44% and trypsin inhibitor, 6.32 to 11.58 TI unit/g. There were significant differences (p